Market Survey of Shrimp Feed in Gujarat - Rajak, Sujeet; Sharma, Arpita; Ananthan, P.S (Indian Journal of Marketing, 2006)
Cultured shrimps contribute significantly to the total shrimp exports from India. East coast states of India are well developed and organize states in shrimp cultured whereas, West coast states are emerging in this field. A study was performed in Gujarat with objectives of market research and developing a strategy for market entry of shrimp feed in the state. Data was collected from secondary sources and with help of a questionnaire. Out of 14 coastal districts of Gujarat; Valsad, Navasari, Surat and Bahruch were selected for study. It was found from study that total feed requirement of Gujarat is 4000 ton; most of the farmers prefer feed on credit. Dealers give credit according to financial status and repayment capacity of farmers. Giving credit to farmers also depends upon the relation between farmers and dealers. Farmers usually don’t change their feed brand unless they suffer very big loss of crop. Farmers believe that composition of different brands is same, but good management practices are needed. Farmers also seek good services and technical support from feed companies. Dealers play main role in creating market of aquafeed because of being in the direct contacts with the farmers.